Does ultraviolet radiation affect the germination of Persian clover seeds? - Stefanello, Raquel; Menna Barreto, Rafaelle Almeida; Garcia, Wagner Jesus da Silva; Dorneles, Lucio Strazzabosco (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
This study aimed to evaluate the influence of ultraviolet light on the germination of Trifolium resupinatum L. seeds (Persian clover). The seeds were exposed to different times (doses) of exposure to UV-B and UV-C light with radiation intensity of 2.5 W m-2. Afterward, they were sown in gerbox boxes with germitest paper and stored in a Biochemical Oxygen Demand at 20°C. Tests such as germination, germination speed index, length and dry mass of seedling were performed. No significant differences were among UV-B light treatments. However, seeds exposed to 8 hours of UV-C light showed a reduction in the germination speed index when compared to control (from 92.5 to 88.7). Furthermore, the length of the seedlings increased by an average of 1.3 cm in relation to the control. Under the conditions of this study, it was concluded that Persian clover seeds exhibit relative tolerance to UV-B radiation while showing some sensitivity to UV-C radiation. The pelleting of the seeds associated with the tegument acted as a physical block, impeding the passage of UV light. The results contribute to our understanding of how Persian clover responds to UV radiation exposure.